Can proficient tertiary learners of English speak persuasively? A discovery of skills, mistakes and problems - Abdul Latiff@Bapoo, Lili Suriani (2022)
Speaking persuasively is a skill needed in social and workplace communication contexts. Even though the importance of using appropriate language discourse in persuasion has been acknowledged since the time of ancient Greek, persuasive speaking strategies are not commonly taught to students who speak English as their second language. Information on the metadiscourse used by proficient second language speakers of English when speaking to persuade, also needs to be obtained. Hence, the persuasive strategies of 30 proficient undergraduates who were studying English for International Communication at an English medium university in Malaysia were investigated using Hyland’s (2005) interpersonal model of metadiscourse. The students’ short persuasive speeches were recorded and their use of interactive and interactional metadiscourse to show the Aristotelian rhetorical appeals of logos, ethos and pathos were analyzed. Focus group discussions were also conducted after a 14-week persuasive speech course to gather information on the students’ thoughts about their own abilities to speak persuasively before they attended the course. Findings show that the students could speak with appeals to emotion, but improvements are needed to build well supported arguments and to display credibility of the speaker. In the focus group discussions, the students mentioned that prior to the course, they were not mindful of word choice, politeness, and ethics. They also felt that they had failed to focus on the audience. Moreover, they highlighted their initial problems in differentiating informative from persuasive speeches, applying good presentation skills, using appropriate persuasive appeals; and displaying confidence. These findings imply that due to the complex relationship between language and psychological factors in persuasion, speaking persuasively can be difficult even for proficient second language learners of English. Hence, instructors for language, communication and psychology courses should collaborate to come up with a persuasive speech course for tertiary learners to enhance their speaking skills.